Microbial biosorbent for remediation of dyes and heavy metals pollution: A green strategy for sustainable environment - Tripathi, Manikant; Singh, Pankaj; Singh, Ranjan; Bala, Saroj; Pathak, Neelam; Singh, Sangram; Chauhan, Rajveer Singh; Singh, Pradeep Kumar (Frontiers in Microbiology, 2023)
Toxic wastes like toxic heavy metals and dyes has been released into the environment as a direct result of industrialization and technological progress. Biosorption of contaminants utilize a variety of biomaterials. Biosorbent can adsorb toxic pollutants on their surface through various mechanisms like complexation, precipitation, etc., for the elimination of both inorganic and organic substances. The effectiveness of the biosorbent is influenced by the number of accessible sorption sites on its surfaces. Biosorption's low cost, high efficiency, lack of nutrient requirements, ability to regenerate the biosorbent, are its main advantages over other treatment methods. Optimization of environmental conditions like temperature, pH, nutrients availability and other factors are prerequisite to achieve optimal biosorbent performance. Recent strategies include nanomaterials, genetic engineering and biofilm based for effective remediation of various types of pollutants. The removal of hazardous dyes and heavy metals from wastewater using biosorbents is a strategy that is both efficient and sustainable.